SEMANTIC ANALYSIS OF GENDER UNITS IN THE ENGLISH LANGUAGE (Journal of Universal Science Research, 2025)
The article describes the context of evolving linguistic norms influenced by sociocultural shifts, such as the increasing push for gender inclusivity and non-binary representation in language. Analyzing gender units semantically can help identify implicit biases, asymmetries, and stereotypes embedded in the language, contributing to efforts aimed at reducing gender discrimination in communication.